Practical Methods of Implementation for the Indispensable Mechanism of GDPR Compliance - Bańka, Michał; Soczyński, Tomasz; Wasiak, Dariusz (University of Wroclaw. Faculty of Law, Administration & Economics, 2021)
New quality that has been delivered by the provisions of General Data Protection Regulation (GDPR) (EU) 2016/679 is intended to secure a higher level of safety for personal data processing operations. The following elaboration was produced as an attempt to address the questions regarding practical methods of implementation for the indispensable mechanism of GDPR compliance. The guidelines contained in the article are supposed to be helpful in enhancing the safety level for processed personal data. Theoretical and legal studies over the status and functioning of the valid legislation with reference to the practical application of personal data processing procedures have been applied in the article. The main sources of knowledge included valid legal acts, opinions from Article 29 Working Party, technical norms as well as available general knowledge. The outcomes of the said studies indicated the complexity of the issue and established the necessity to continue further studies in practical implementation methods, such as the national and European mechanism of certification or sector codes of good practices.
Keywords: GDPR; personal data breach; EU Data Protection Regulation; notification requirement; mandatory data breach notification; security breach notification; proceeding pseudonymization; anonymization encryption of personal data; proceeding system recovery and testing; business continuity plan